The Role of Critical Reading Skills in Finding Moral Messages in Reading - Maharani, Siti Sabrina; Salsabila, Siti Naida Aulia; Junarsih, Imas; Ratnasari, Dine Trio; Maulana, Ipan (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
This study aims to improve the critical reading skills of grade VI A students of SDN 1 Malabar in finding moral messages in reading. The research method used is qualitative observation-based, with direct observation of the learning process in the classroom. The results of the study indicate that most students have been able to analyze texts, draw conclusions, and convey ideas in writing, but there are still 50% of students who need further attention and guidance to improve their critical reading skills. Factors such as learning experience, learning environment, and cognitive abilities influence students' critical reading skills. This study suggests the importance of strengthening critical reading skills in Indonesian language learning to improve students' ability to find moral messages in reading.